The Ideas And Practices Of Interactive Foreign Language Instruction - Saidova Maʼmura Sulaymonovna, (European Journal of Life Safety and Stability (2660-9630), 2022)
The English language is extremely vital today. Because everyone now has the possibility to pursue higher education overseas, an increasing number of people require English in order to attend universities and colleges. New concepts in science and health emerge at such a rapid pace that it is hard to translate everything into multiple languages. The interchange of scientific, technological, and cultural knowledge broadens and strengthens international ties. Foreign language instruction is a matter of state importance in this circumstance.